Five challenges to reconcile agricultural land use and forest ecosystem services in Southeast Asia. Issue 5 (20th August 2016) - Carrasco, L.R.; Papworth, S.K.; Reed, J.; Symes, W.S.; Ickowitz, A.; Clements, T.; Peh, K.S.‐H.; Sunderland, T.
Abstract: Southeast Asia possesses the highest rates of tropical deforestation globally and exceptional levels of species richness and endemism. Many countries in the region are also recognized for their food insecurity and poverty, making the reconciliation of agricultural production and forest conservation a particular priority. This reconciliation requires recognition of the trade‐offs between competing land‐use values and the subsequent incorporation of this information into policy making. To date, such reconciliation has been relatively unsuccessful across much of Southeast Asia. We propose an ecosystem services (ES) value‐internalization framework that identifies the key challenges to such reconciliation. These challenges include lack of accessible ES valuation techniques; limited knowledge of the links between forests, food security, and human well‐being; weak demand and political will for the integration of ES in economic activities and environmental regulation; a disconnect between decision makers and ES valuation; and lack of transparent discussion platforms where stakeholders can work toward consensus on negotiated land‐use management decisions. Key research priorities to overcome these challenges are developing easy‐to‐use ES valuation techniques; quantifying links between forests and well‐being that go beyond economic values; understanding factors that prevent the incorporation of ES into markets, regulations, and environmental certification schemes; understanding how to integrate ES valuation into policy making processes, and determining how to reduce corruption and power plays in land‐use planning processes.